2017
DOI: 10.1016/j.jvs.2016.08.100
|View full text |Cite|
|
Sign up to set email alerts
|

Sex differences in mortality and morbidity following repair of intact abdominal aortic aneurysms

Abstract: Objective Medicare studies have shown increased perioperative mortality in women compared to men following endovascular and open AAA repair. However, a recent regional study of high-volume centers, adjusting for anatomy but limited in sample size, did not show sex to be predictive of worse outcomes. This study aims to evaluate sex differences after intact AAA repair in a national clinical registry. Methods The Targeted Vascular module of NSQIP was queried to identify patients undergoing EVAR or open repair f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 37 publications
11
93
0
4
Order By: Relevance
“…A recent study using the English National Health Service (NHS) administrative data set and UK National Vascular Registry data demonstrated that in‐hospital mortality following elective as well as ruptured AAA is worse in women; this confirmed the findings of previous studies that used national databases and registries, and demonstrated higher mortality rates following repair of AAA among women. A recent economic evaluation supported by clinical outcome data from an administrative data set and national registry reported that screening women for AAA is not cost‐effective under various scenarios, including starting screening at an older age.…”
Section: Introductionsupporting
confidence: 74%
“…A recent study using the English National Health Service (NHS) administrative data set and UK National Vascular Registry data demonstrated that in‐hospital mortality following elective as well as ruptured AAA is worse in women; this confirmed the findings of previous studies that used national databases and registries, and demonstrated higher mortality rates following repair of AAA among women. A recent economic evaluation supported by clinical outcome data from an administrative data set and national registry reported that screening women for AAA is not cost‐effective under various scenarios, including starting screening at an older age.…”
Section: Introductionsupporting
confidence: 74%
“…However, this sex difference was not noted at 5 years. Although previous studies 33,34 highlighted the higher initial perioperative mortality in women, the 5-year mortality did not confirm this 34,35 . This is possibly due to other competing factors, including increasing age, co-morbidities and type of repair, in line with other studies 36 .…”
Section: Discussionmentioning
confidence: 66%
“…A retrospective cohort study 36 These studies have several limitations. First and foremost, factors that might confound the comparison of men and women, such as age, aneurysm diameter, and comorbidities, were inconsistently reported.…”
Section: Schermerhorn Et Al (2012) 30mentioning
confidence: 99%